The Perception of English Study Program Students of FKIP Universitas Riau toward Using Grammarly in Writing Essay - Kusumaningrum, Amalia; Eliwarti; M. Syarfi (Institut Agama Islam Negeri Palopo, 2025)
Grammarly is one of the famous Automated Writing Evaluation (AWE) tools used by many students. Many studies reveal that this tool can improve students' writing skills. This research aims to find out and describe the perception of English Study Program Students of FKIP Universitas Riau toward using Grammarly in writing essay. This research used quantitative methods. Questionnaires were used to collect data regarding students' perceptions of using Grammarly in Writing Essay. The research results showed that many students chose to use Grammarly because they felt it was important to get input from Grammarly, they lacked confidence in writing because Grammarly can correct mistakes in their writing. Students believed that the benefits of Grammarly can improve their writing skills, solve language problems, and encourage them to do proofreading independently. Students rated Grammarly's strengths, including correctness features to improve spelling, punctuation, and make writing interesting and varied. In addition, it helped students save time in writing corrections. On the other hand, only a few students felt that Grammarly required a stable internet connection to function properly and required additional corrections as some entries were deemed inaccurate. Students responded to these errors by constantly rechecking and ensuring their Grammar input fits the context of their writing, or they will ignore inaccurate input. Students kept using Grammarly because it helped them improve their writing despite some shortcomings.